Work Motivation as a Moderator of Organizational Commitment and Competence on Employee Performance - Mahantara Nugraha, Rizal; Wimbo, Mursito; Ikhsan, M. (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This research focuses on the influence of organizational commitment and competence on employee performance by considering the role of work motivation moderation in the ASN environment. The purpose of this study is to find out and analyze the relationship between organizational commitment and competence and employee performance as well as the role of work motivation as a moderator. This research method uses quantitative, by distributing questionnaires to ASN in Klojen District and data analysis using multiple linear regression with moderation after conducting various validity tests and classical assumptions. The results of this study prove that: first, organizational commitment affects employee performance; second, competence affects employee performance; third, work motivation strengthens the influence of organizational commitment on employee performance; and fourth, work motivation strengthens the influence of competence on employee performance. This research has implications for the importance of increasing organizational commitment and competence and paying attention to work motivation to improve employee performance